Fatalities in road traffic, a result of accidents or suicides - Anna-Lena Andersson (19774452) (2015)
Since 2010, Sweden presents suicides in road traffic separately from fatalities caused by accidents. The aim with this study was to assess the number of road traffic suicides by studying the fatality from three angles; the vehicle, the road and the road user. The main focus was to develop and perform a psychosocial examination of the road user. First, a method was developed for classification of road fatalities to determine if they were caused by accident or suicide and criteria was developed for selection of cases that are to undergo the classification process. The examination of the road user was performed in cooperating with accident investigators at the Transport Administration, the police, relatives, witnesses, as well as with information from autopsy reports, and case records from earlier medical service. During 2012, an investigator in behavioural science, experienced from counselling at hospitals conducted the examinations. The suspected suicides were classified by an expert group of five persons with knowledge in forensic medicine, psychology and traffic safety using the classification system. First, the classification was made without the psychosocial examination. A second classification was performed with the additional psychosocial information. Forty-nine cases were studied. In 2012, twenty-two (7%) cases were classified as suicides without the psychosocial information and thirty-six (11%) with all information included. The unclear cases were reduced from 20 to 8. From 2013 and forward the classifications were made only once with all information. In 2012-2014, 89 (10%) fatalities were classified as suicides. Year 2010-2011, when the classifications were made without additional psychosocial information, 6% of the fatalities were classified as suicides [Skyltfondsprojekt;TRV2011-13351]. By including psychosocial factors in the classification of suspected suicides the number of unclear cases were reduced. In order to work with suicide prevention the size and the pattern of the problem must be known. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.27